A highly fluorescent turn-on probe in the near-infrared region for albumin quantification in serum matrix. Issue 60 (12th July 2018) - Chakraborty, Goutam; Ray, Alok K.; Singh, Prabhat K.; Pal, Haridas
Abstract : A commercially available styryl based fluorophore in the near-IR region shows exceptional turn-on emission for serum albumins. Abstract : Developing sensitive and selective near-infrared fluorescent bio-probes for serum albumin detection is an ambitious and highly rewarding task. Herein, we report a styryl based fluorophore for serum albumin detection, which displays an exceptional turn-on emission enhancement of ∼500 fold, the highest reported so far in the near-infrared region, and more importantly enables quantification of albumin in the complex serum matrix.